A Comparative study on lipase enzyme immobilized on acid and glutaraldehyde functionalized multiwalled carbon nanotubes - Jameel, Ahmed Tariq; Arif, Muhammad Arif (Thai Society for Biotechnology (TSB) & Asian Federation of Biotechnology (AFOB), 2017)
Nanomaterials are being increasingly employed as support materials for enzyme immobilization owing to their biocompatibility and large surface area. Immobilization of lipase on multiwalled carbon nanotubes (MWCNT) has shown significant enhancement in the enzyme stability with respect to temperature and pH variations. Functionalization of MWCNT results into cross linking of enzyme with the MWCNT. The present study focused on the comparative performance evaluation of the immobilized lipase on MWCNT functionalized using acid and glutaraldehyde, respectively. Acid treatment of MWCNT will cause lipase to physically adsorb on MWCNT while glutaraldehyde treatment will act as a cross linker and form a covalent bond between lipase and the functionalized MWCNT. Immobilization efficiency was assessed by comparing enzyme loading for the two differently functionalized MWCNTs. Enzyme loading is defined as the ratio of the enzyme that is attached to the MWCNT to the enzyme present in the original enzyme solution. Glutaraldehyde-MWCNT (GL-MWCNT) cross-linking showed 96% of loading efficiency while acid treatment showed 94% efficiency. The maximum enzyme activity on GA-MWCNT was obtained at 45°C and pH 7 while acid-MWCNT showed highest activity at 40°C and pH 8. Enzyme activity was higher for lipase immobilized on GA-MWCNT compared to acid-MWCNT possibly owing to greater enzyme loading in the former support. Immobilized enzyme showed higher relative activity compared to the free enzyme. Lipase on GA-MWCNT showed greater stability at higher pH and temperature compared to that of the acid-MWCNT. Further, lipase on GA-MWCNT exhibited almost 81% residual activity after 5 consecutive uses. In short, GA-MWCNT appears to be a better support material for lipase performance in terms of operational stability, enhanced activity and high residual activity upon multiple uses.